Scale morphology and phylogenetic character mapping of scale-surface microstructures in sixteen Aphanius species (Teleostei: Aphaniidae). (April 2019) - Esmaeili, Hamid Reza; Zarei, Fatah; Sanjarani Vahed, Nafiseh; Masoudi, Mojtaba
Highlights: Based on the result of phylogenetic character mapping: Scale surface microstructure cannot be used for the species identification and inferring phylogenetic relationships in the genus Aphanius . It confirms previous studies on cichlids and cyprinids, indicating that the scale shape varies with age and size of the fish. The polygonal state in the scales of Aphanius species was a primitive shared character state. Abstract: Recent studies on the analysis of the evolutionary relationships between the various taxa of the teleost fishes are based on the evaluation of the efficacy of different approaches, verifying the taxonomical congruence between the hypotheses inferred from molecular data and those from morphological data. The first objective of this study was to investigate the macro- and microscopic characterization of the body key scales for the sixteen Aphanius species, and to discuss their taxonomic significance. In addition, to reveal the phylogenetic origins of particular adaptations and to identify a possible cases of convergent evolution in scales of Aphanius species, we used a phylogenetic character mapping procedure that uses an independent data source, namely molecular data that is presumed to be functionally independent of the scale traits. Comparison of the resulted phylogenetic trees and scale data dendrogram implied that neither scale shape/scale surface morphology, nor scale surface microstructure can be used for the species identification and inferring phylogenetic relationships in the genus Aphanius . This conclusion confirms previous studies, indicating that the scale shape and ornamentations varies with habitat, age and size of the fish. We also concluded that the polygonal state in the scales of Aphanius species was a primitive shared character state.